The Medial Thalamus Plays an Important Role in the Cognitive and Emotional Modulation of Orofacial Pain: A Functional Magnetic Resonance Imaging-Based Study - Jin, Yu; Yang, Hong; Zhang, Feifei; Wang, Jue; Liu, He; Yang, Xin; Long, Hu; Li, Fei; Gong, Qiyong; Lai, Wenli (Frontiers in Neurology, 2021)
The thalamus plays a critical role in the perception of orofacial pain. We investigated the neural mechanisms of orofacial pain by exploring the intrinsic functional alterations of the thalamus and assessing the changes in functional connectivity (FC) between the thalamic subregions with significant functional alterations and other brain regions in orofacial pain using the seed-based FC approach. There were 49 participants in the orofacial pain group and 49 healthy controls. Orofacial pain was caused by orthodontic separators. The resting-state functional magnetic resonance imaging data of the two groups were analyzed to obtain the fractional amplitude of low-frequency fluctuations (fALFF) of the thalamus; the thalamic subregions with significant fALFF abnormalities were used as seeds for FC analysis. Student’s t-tests were used for comparisons. Pearson’s correlation analysis was performed using SPM software. Forty-four participants with orofacial pain (mean age, 21.0±0.9 years; 24 women) and 49 age- and sex-matched healthy controls (mean age, 21.0±2.6 years; 27 women) were finally included. Compared with the control group, the orofacial pain group demonstrated the following: (1) increased function in the dorsal thalamus and decreased function in the medial thalamus; (2) decreased FC between the medial thalamus and 12 brain regions (p<0.05, family-wise error corrected, voxel>100); and (3) potential positive and negative correlations between the medial thalamus-seeded FC and visual analogue scale score changes (p<0.05, AlphaSim corrected). The findings show that the medial and dorsal thalami play important roles in orofacial pain perception, and that the medial thalamus likely plays an important role in the cognitive and emotional modulation of orofacial pain.